If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 6 + -2(x + -3) Reorder the terms: 3 = 6 + -2(-3 + x) 3 = 6 + (-3 * -2 + x * -2) 3 = 6 + (6 + -2x) Combine like terms: 6 + 6 = 12 3 = 12 + -2x Solving 3 = 12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 2x = 12 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 2x = 12 + 0 3 + 2x = 12 Add '-3' to each side of the equation. 3 + -3 + 2x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 12 + -3 2x = 12 + -3 Combine like terms: 12 + -3 = 9 2x = 9 Divide each side by '2'. x = 4.5 Simplifying x = 4.5
| y=-x^2+16 | | 15y-8=10y+2 | | 5x+7=3(x+4) | | .74=11612000-x/5246000 | | 1+192837465x-d=231111111116666666 | | 4/b-7/d= | | 55x-9+g=100007 | | 4/(x-6)=5 | | 55x-9+g= | | 3t+19-5t=91 | | z^2(4z^3-10)=0 | | u/4=0 | | 5p^2+30x=0 | | 4x-1=2(x-5) | | 5c+17-8c=156 | | 2=p/6 | | 5/60=w/10 | | 4x-1=2(x-3) | | 345=874-x/874 | | 9r+9= | | 2x-1/4x=(-28) | | 3/4d=18 | | 7(x+8)+4=-9(x-9)-1 | | 2s+a=447 | | 3/8d=6 | | X+11x+2=0 | | 3(4x+1)=9(3x-5) | | 6x-4=5(x+3)+7 | | 3x^2-18x=48 | | 81x^3+324x^2-x-4=0 | | 7x-8-4x=25 | | y=-3/5x-4/5 |